50 THINGS YOU CAN DO TO SAVE THE WORLD - Hankinson, Kim (New York, NY : Racehorse for Young Readers, 2020)
"Calling all bold, brave, green, heroic, caring, daring, dreaming, mindful, shouting, creative, rescuing, resourceful Earth warriors! Full of super creative ideas and activities, this book will help you fight the effects of climate change, reduce carbon emissions, and help save the planet. Learn to: Make a megaphone or kite to spread the word! Reduce water usage and food waste! Cut down on meat consumption! Make a
Keywords: Environmentalism -- Juvenile literature; Environmental protection -- Juvenile literature; Environmental protection; Juvenile works; Juvenile literature